Optimizing Raw Material Inventory Costs at the Corporate Macro Level: A Financial EOQ Approach and Risk Mitigation at PT. Mayora Indah Tbk (2024–2025) - Rafi Rasidin; Asri Sundari; Garneta Dinarsuci; Shahnawaaz Kiara Amanda; Suci Fitrianti (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study evaluates the adequacy of public data for applying Economic Order Quantity (EOQ), Safety Stock (SS), and Reorder Point (ROP) to PT Mayora Indah Tbk’s inventory for the 2024–2025 period. Research Method: This study employs a descriptive quantitative approach with a documentary design. The data were drawn from consolidated financial statements and sustainability reports, and were then evaluated based on physical data requirements, relevant costs, demand, and lead time. Results and Discussion: The public report provides only aggregate inventory values and does not disclose quantities, ordering costs, storage costs, or lead times for each material. The insurance coverage amount is not the annual premium, and data do not support the ordering frequency and previous SS parameters. Therefore, the estimates for EOQ, ROP, cost savings, and margin improvement cannot be validated. Implications: Applying the model requires transaction data at the homogeneous material level, including physical usage, incremental costs, order history, lead times, and service targets. The research findings serve as the basis for improving inventory data management and for subsequent implementation studies. Originality: This study highlights the methodological limitations of using consolidated financial statements to make operational EOQ decisions at large-scale FMCG companies.